Ayurvedic Perspective of Polycystic Ovarian Syndrome (International Journal of Ayurveda and Pharma Research, 2022)
Polycystic Ovarian Syndrome is the leading cause of female infertility in the present scenario. It is one of the important reproductive endocrine disorders in the world. The various conditions associated with PCOS show similarities with Gulma, Prameha, Sthoulya, etc. Pushpagni Jaataharini mentioned in Kasyapa Samhita bears some similarities with clinical presentations of this disease. Nashtarthava, Arthavakshaya, and Vandhya yoni Vyapath mentioned in Susrutha Samhita can also be taken into account. As PCOS is a metabolic disorder, there is impairment of the function of Agni at various levels. The disease can be considered as a Bahudoshavastha. It begins as a Vata imbalance, which pushes Kapha and Pitta out of balance in the Arthavavaha Srothas. Samsodhanam, use of Agneya Dravyas, use of Swayoni Vardhana dravyas, and avoidance of etiological factors is the main treatment principle.Ayurvedic classical textbooks along with available modern literature were referred to make a clear understanding of the concept of Polycystic Ovarian Syndrome. The clinical symptoms of Polycystic Ovarian Syndrome like amenorrhea and hyperprolactinemia are seen in Rakthagulma. The clinical manifestation and pathology of the disease are very close to that of Prameha. Nashtarthava explained by Acharya Susrutha mentions that due to Vatha Kapha Avarana, Arthavanasha occurs in females. This can be correlated with amenorrhoea associated with Polycystic Ovarian Syndrome. In Vandhya yonivyapath, arthava is destroyed. This can be considered secondary amenorrhoea or anovulation which ultimately causes the inability to conceive a child.